Господарсько-побутовий комплекс та проблеми вивчення структури пізньопалеолітичних пам'яток - Кротова, О.О. (Археологія, 2002)
У статті розглянуто питання історіографії вивчення структури пізньопалеолітичних пам'яток, методів та методологічних підходів да просторового аналізу в первісній археології, показано значення поняття господарсько-побутового комплексу для сучасних досліджень, наведено кілька прикладів вивчення структури стоянок та реконструкції поведінки людей на їх площі. В статье рассмотрены вопросы историографии пространственного анализа в первобытной археологии, дан анализ основных методологических подходов к изучению структуры позднепалеолитических памятников — археологического и этноархеологического. Показано значение понятия хозяйственно-бытового комплекса (введенного И.Г. Шовкоплясом) для современных исследований. Рассмотрена структура и описана реконструкция использования территории обитателями нескольких позднепалеолитических стоянок бассейна Северского Донца, интерпретируемых как хозяйственно-бытовые комплексы или недолговременные базовые лагеря небольших групп охотников-собирателей. The article is dedicated to considering the historiography of the spatial analysis in Prehistoric Archaeology. The characteristic of the main methodological approaches (archaeological and ethnoarchaeological) to studying the structure of the Upper Paleolithic sites is given. The importance of the economic-domestic complex (formulated by I. Shovkoplyas) for modern research is underlined. The author also analyses the structure of the economic-domestic complex and reconstructs the process of utilization of the territory of the Severski Donets basin by the inhabitants of some Upper Paleolithic sites. The sites are interpreted as the short-term base camps of the small groups of hunter-gatherers.